The prognostic value of admission D-dimer level in patients with cardiogenic shock after acute myocardial infarction - Jiang, Yi; Zhu, Yuansong; Xiang, Zhenxian; Sasmita, Bryan Richard; Wang, Yaxin; Ming, Gong; Chen, Siyu; Luo, Suxin; Huang, Bi (Frontiers in Cardiovascular Medicine, 2023)
Background: Shock is associated with the activation of the coagulation and fibrinolysis system, and D-dimer is the degradation product of cross-linked fibrin. However, the prognostic value of D-dimer in patients with cardiogenic shock after acute myocardial infarction remained unclear. Results: Among 218 patients with CS complicating AMI, those who died during the 30-day follow-up presented with worse baseline characteristics and laboratory test results, including a higher level of D-dimer. According to the X-tile program result, the continuous plasma D-dimer level was divided into 3 gradients. The 30-day all-cause mortality in patients with low, medium, and high levels of D-dimer were 86.2%, 53.3%, and 22.4%, respectively (p<0.001). The 30-day incidence of MACE were 89.7%, 77.0% and 46.3%, respectively (p<0.001). In multivariable Cox regression model, the trilogy of D-dimer level was an independent risk predictor for 30-day mortality, similar result was observed in MACE. The RCS analyses suggested non-linear associations of D-dimer with 30-day mortality. The enrollment of D-dimer improved risk discrimination for all-cause death when combined with the traditional CardShock score (C-index: 0.741 vs. 0.756, p-difference<0.001) and the IABP-SHOCK II score (C-index: 0.732 vs. 0.754, p-difference<0.001). Similar results were acquired after logarithmic transformed D-dimer was included in the risk score. The improvements in reclassification which were calculated as additional net reclassification index were 8.6% and 7.5%, respectively. Conclusions: Admission D-dimer level was independently associated with the short-term outcome in patients with CS complicating AMI and add of D-dimer brought incremental risk prediction value to traditional risk prediction scores.